2017
DOI: 10.1016/j.stemcr.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Expression and Epigenetic Signatures in Hepatocyte-like Cells Produced by Different Strategies from the Same Donor

Abstract: SummaryHepatocyte-like cells (HLCs) can be generated through directed differentiation or transdifferentiation. Employing two strategies, we generated induced pluripotent stem cell (iPSC)-HLCs and hiHeps from the same donor cell line. Both types of HLCs clustered distinctly from each other during gene expression profiling. In particular, differences existed in gene expression for phase II drug metabolism and lipid accumulation, underpinned by H3K27 acetylation status in iPSC-HLCs and hiHeps. While distinct phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Downregulated DEGs were associated with cell cycle, systemic lupus erythematosus, alcoholism, DNA replication, and viral carcinogenesis pathways, indicating that differentiation reduced the cell proliferation and tumorigenicity risk. Additionally, from the enriched KEGG pathways of upregulated DEGs in HLCs/hHF-iPSCs and HLCs/PHHs groups, we found that the induced HLCs further repressed the downregulated pathways, consistent with the PHHs/hHF-iPSCs group; however, the pathways of alcoholism, cell cycle, and systemic lupus erythematosus continued to be downregulated, and the complement and coagulation cascades, metabolic pathways, drug metabolism-cytochrome P450, and steroid hormone biosynthetic pathway-associated DEGs needed to be increased [ 8 ]. Although our experiments confirmed that the HLCs we obtained mimicked the synthesis and metabolism functions of the liver, our data analysis supported that they needed to be further improved.…”
Section: Discussionsupporting
confidence: 59%
“…Downregulated DEGs were associated with cell cycle, systemic lupus erythematosus, alcoholism, DNA replication, and viral carcinogenesis pathways, indicating that differentiation reduced the cell proliferation and tumorigenicity risk. Additionally, from the enriched KEGG pathways of upregulated DEGs in HLCs/hHF-iPSCs and HLCs/PHHs groups, we found that the induced HLCs further repressed the downregulated pathways, consistent with the PHHs/hHF-iPSCs group; however, the pathways of alcoholism, cell cycle, and systemic lupus erythematosus continued to be downregulated, and the complement and coagulation cascades, metabolic pathways, drug metabolism-cytochrome P450, and steroid hormone biosynthetic pathway-associated DEGs needed to be increased [ 8 ]. Although our experiments confirmed that the HLCs we obtained mimicked the synthesis and metabolism functions of the liver, our data analysis supported that they needed to be further improved.…”
Section: Discussionsupporting
confidence: 59%
“…We further compared the global gene expression between freshly thawed PHHs and ProliHHs cultured in normoxia by RNA sequencing analysis. To verify the extent to which ProliHHs maintained hepatic gene expression, we used HLCs derived from human pluripotent stem cells (hiPSC-Hep) or from human somatic cells by direct transdifferentiation (hiHep) as controls (Gao et al, 2017). Notably, principal-component analysis (PCA) and hierarchical clustering revealed that ProliHHs formed an associated group and were distinct from other cells ( Figures 2C and S4A).…”
Section: Prolihhs Partially Maintain Features Of Hepatocytesmentioning
confidence: 99%
“…This method was able to generate large numbers of functional HLCs capable of rescuing liver failure in mice after transplantation. Nevertheless, human HLCs showed limited engraftment capability in mouse livers (Gao et al, 2017;Ji et al, 2013). The repopulation efficiency of HLCs, which is around 2%, is far lower than that of PHHs, which is around 70% (Ji et al, 2013;Rezvani et al, 2016;Sampaziotis et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, protocols to differentiate ES/iPS cells into hepatocytes, hereafter iHep, has also evolved substantially over time; however, the degree of maturity is still far from that of freshly isolated PHH. [284][285][286][287] For example, transcriptome analysis of iHep demonstrated a highly distinctive gene expression profile compared with that of PHH. 284 These important observations collectively indicate that there remains a significant gap in terms of the degree of differen-tiation/maturation between genuine hepatocytes and iHeps.…”
Section: Regenerative Biologymentioning
confidence: 99%
“…[284][285][286][287] For example, transcriptome analysis of iHep demonstrated a highly distinctive gene expression profile compared with that of PHH. 284 These important observations collectively indicate that there remains a significant gap in terms of the degree of differen-tiation/maturation between genuine hepatocytes and iHeps. Of great interest, it has been shown that the implantation of iHep into the liver of HLCM prompted engraftment, proliferation, and further maturation.…”
Section: Regenerative Biologymentioning
confidence: 99%